Student Character Education Model Development in the Era Industry 4.0 - Muh Hasan Marwiji; Aan Hasanah; Bambang Samsul Arifin (Universitas Muhammadiyah Enrekang, 2023)
Entering the 4.0 era raises new problems, internet-based communication technology that can be accessed via smartphones has become an important and inseparable part of everyday millennial life. The negative impact of technological developments is moral degradation. Moral degradation from the influence of the internet is very likely to occur because access to internet content without age limits has a negative impact on children. This study aims to find a model of character education in schools for students in the 4.0 era. Character education in the 4.0 era needs adaptation to trends and new challenges that arise. The research method used is a qualitative method by applying literature study. The results of the study show that aspects that need attention in character education in the 4.0 era: Digital Literacy, Collaboration Skills, Creativity and Innovation, Digital Ethics, Independence and Lifelong Learning Ability, Empathy and Social Connectivity, Ethical Problem Solving. character education for generation 4.0 students, namely: Technology-Based Character Education Model, Project and Innovation-Based Character Education Model, Entrepreneurship-Based Character Education Model, Character-Based Education Model Problem Solving Digital, Character Education Model Based on Digital Communication Skills.